Penerapan Model Pembelajaran Jigsaw Berbasis Project Based Learning dalam Meningkatkan Keterampilan dan Hasil Belajar Siswa SMK - Prasojo, Krisna Tri; Huda, Khoirul; Kriswanto, Kriswanto; Kristiawan, Ruben Bayu; Laksono, Galih Tri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to implement and test the effectiveness of the jigsaw learning model based on project based learning in improving students' skills and learning outcomes in the subject of lathe machining at SMK Negeri 5 Sukoharjo. The method used is a quasi-experimental design with a two-group pre-test post-test design, involving 68 students divided into an experimental group and a control group. Data collection was carried out through pre-test and post-test, observation, and documentation. The results of the analysis showed a significant increase in the experimental group's learning outcome score with an average post-test score of 79.85 or an increase of 34.07% compared to the average pre-test score of 59.56. In contrast, the control group only experienced an increase of 28.3%, from an average of 55.44 to 71.18. The t-test showed a significant difference between the experimental group and the control group (p <0.05). N-Gain analysis also showed high effectiveness in the experimental group (0.5166) compared to the moderate category in the control group (0.3503). In addition, the observation results showed an increase in motivation, active participation, and student cooperation during the learning process. Thus, the combination of the jigsaw model with project-based learning has proven effective in improving student learning outcomes and skills significantly compared to conventional learning methods. This study contributes to the development of contextual and collaborative vocational learning strategies to face the demands of the industrial world.